Understanding Multicultural Education From Islamic Perspective - Mohamed Adnan, Mohamad Azrien; Mamat, Arifin; Mohd Sabri, Mohamad Zalhan; Osman, Khazri (Jurnal Usuluddin, 2021)
This study explored understanding multicultural education from an Islamic perspective, as well as how society is integrated in Islam. One of the main features brought by Prophet Muhammad (PBUH) during his lifetime was the integration of society, as he was the one who constructed a peaceful society in the Islamic Era when Muslims, Arabs, Christians, and Jews coexisted. This study looked also at the benefits and shortcomings of multicultural education. The question is not whether multicultural education should be implemented, but rather what we mean by it and how we would go about implementing such a change inside an educational system.